Doe, Norman; Ombres, Robert, English Canon Law. Essays in Honour of Bishop Eric Kemp, Cardiff 1998 [Rezension] - Christensen, Katherine (1999)
Aufnahme: BO Z 882
Keywords: Church of England; Kirchenrecht; Rezension